(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The Experimental Analysis of Behavior has been challenged to explore, in terms of concepts and methods, how stimuli, or stimuli relations, come to control certain behavior. The research on equivalence and stimuli class formation has extended the discipline horizons on relational responding, especially when the phenomenon occurs in the context of language and symbolic behavior. From the initial researches on equivalence till those conducted nowadays, a great amount of empiric data has been produced and some theoretical formulations have been elaborated. The present work, which has theoretical and didactic purposes, shows a generic account of the development of the relational responding concept, emphasizing the need of deep attention to the training procedures that lead to the establishment of stimulus control of such responding.